EXPERIMENTAL STUDY OF COOLING FLUID VARIATION ON THE THERMOELECTRIC HOT SIDE ON THERMOELECTRIC VACCINE COOLER BOX PERFORMANCE - Pratama, Novreza; Rosyadi, Imron; Wahyudi, Hadi; Fasya, M. Haykal (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The advanced countries make health a high priority and collaborate to create a better quality of life. Vaccination is a critical component of global health. Vaccines must be stored at a constant temperature of 2-8℃, to maintain the viability of the vaccine cold chain. Thermoelectric cooling systems (TECs) are a solution that is simple, lightweight, low cost, and portable. Excessively high hot-side temperatures can be detrimental to operators and the environment during distribution processes. The application of fans and circulating fluid can reduce the TEC hot-side temperature. The lowest TEC temperature difference of 30.26℃ is achieved by using only a fan. The minimum hot side of 31.28℃ is achieved with the fan and circulating water model. The minimum cold side can be increased to 0.53℃ with the fan and circulating radiator coolant model. All tests were at vaccine-eligible temperatures. The best COP of 0.14 can be reached in this study.